Dynamics of the Content of Phenolic Compounds in the Shoots of the Representatives of the Family Cornaceae Bercht. Et J. Presl in the Period of Winter Dormancy - Levon, Volodymyr; Klymenko, Svitlana; Tesliuk, Maxim (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The study of phenolic compounds in shoots of the family Cornaceae Bercht. et J. Presl due to the sharp fluctuations of temperatures during winter dormancy. Analysis of the obtained experimental data showed that the species and varieties of the family Cornaceae differ significantly in content of phenolic compounds in the period of sharp fluctuations of temperatures. Detailed analysis of the graphic depends of the content of phenolic compounds in the shoots of plants of the family Cornaceae of the average daily temperature in the period of winter dormancy, it has been noticed quite a lot of differences in the dynamics of accumulation of phenols in different species of the genus Cornus L. and Cynoxylon Raf. Were established in the shoots of Cornus mas L. dynamics of the content of phenolic compounds in the period under study has wider amplitude than that of Cornus officinalis Sieb. et Zucc. and Cornus sessilis Torr. This is consistent with the fact that Cornus mas is an indigenous species that is well adapted to the conditions of Northern Forest-Steppe of Ukraine and is the most winter-hardy of all studied species. It is established that Cynoxylon japonica Nakai has a larger amplitude in the content of phenols in the temperature change unlike Cynoxylon florida L., where the change in the accumulation of phenols occurs more smoothly. Cynoxylon japonica responds to more short-term changes in temperature contrast Cynoxylon florida, where the changes of accumulation of phenolic compounds occur only during prolonged cold snaps, or warming. All this indicates a higher frost resistance Cynoxylon japonica in relation to Cynoxylon florida.